The Evolving Clinical Management of Genitourinary Cancers Amid the COVID-19 Pandemic - Izadmehr, Sudeh; Lundon, Dara J.; Mohamed, Nihal; Katims, Andrew; Patel, Vaibhav; Eilender, Benjamin; Mehrazin, Reza; Badani, Ketan K.; Sfakianos, John P.; Tsao, Che-Kai; Wiklund, Peter; Oh, William K.; et al. (Frontiers in Oncology, 2021)
Coronavirus disease–2019 (COVID-19), a disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, has become an unprecedented global health emergency, with fatal outcomes among adults of all ages throughout the world. There is a high incidence of infection and mortality among cancer patients with evidence to support that patients diagnosed with cancer and SARS-CoV-2 have an increased likelihood of a poor outcome. However, studies on the clinical management of patients with genitourinary cancers during the COVID-19 pandemic are limited. This article discusses the biomedical advances to curb the virus, evolving challenges in the diagnosis, management, and treatment of prostate, bladder, kidney, testicular, and penile cancers at all stages of the patient journey during the first year of the COVID-19 pandemic. Clinically relevant changes imposed as a result of the pandemic, are either primary, due to changes in timing or therapeutic modality; or secondary, due to altered cooperative effects on disease progression or therapeutic outcomes. Here, we provide a review of the epidemiology and biological consequences of SARS-CoV-2 infection in GU cancer patients, as well as the impact of COVID-19 on the diagnosis and management of these patients. We also discuss the use and development of novel and innovative diagnostic tests, therapies, and technology in GU oncology practice amid the pandemic.